2015
DOI: 10.1080/01441647.2015.1069907
|View full text |Cite
|
Sign up to set email alerts
|

E-bikes in the Mainstream: Reviewing a Decade of Research

Abstract: Electric bicycles (e-bikes) represent one of the fastest growing segments of the transport market. Over 31 million e-bikes were sold in 2012. Research has followed this growth and this paper provides a synthesis of the most pertinent themes emerging over the past on the burgeoning topic of e-bikes. The focus is transport rather than recreational e-bike research, as well as the most critical research gaps requiring attention. China leads the world in e-bike sales, followed by the Netherlands and Germany. E-bike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
278
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 360 publications
(286 citation statements)
references
References 45 publications
(64 reference statements)
7
278
0
1
Order By: Relevance
“…Previous research suggests that users of conventional e-bikes are at higher risk of 607 injury than regular cyclists (Fishman & Cherry 2015). The present study showed that students 608 mostly attribute potential safety hazards to other e-bike users rather than to themselves.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…Previous research suggests that users of conventional e-bikes are at higher risk of 607 injury than regular cyclists (Fishman & Cherry 2015). The present study showed that students 608 mostly attribute potential safety hazards to other e-bike users rather than to themselves.…”
mentioning
confidence: 56%
“…Electrically-assisted cycling, or e-biking, is growing in popularity in many countries across 72 the world (Fishman & Cherry 2015). E-bikes combine propulsion by user pedaling with 73 assistance through a computer-guided electric motor.…”
Section: Introduction 71mentioning
confidence: 99%
See 1 more Smart Citation
“…A very important distinction is that the Chinese e-bike market grew very rapidly through the early 2000s, and has since plateaued at around 30 million sales per year [5]. Those e-bikes are relatively low-cost (usually less than $1000 U.S.) and have evolved in form to resemble scooters that are rarely pedaled [6,7]. The market in Western countries has largely maintained bicycle-style form factors with much higher build quality and associated price, with mainstream e-bikes ranging from $800 to $4000.…”
Section: Introductionmentioning
confidence: 99%
“…Western European studies investigate the impact of e-bikes on human health [34] and the environment (e.g., studies in European countries). Additionally, there are studies that focus on the impact of e-bikes on emerging markets and the behavior of this new market [14] (e.g., studies conducted in North-America).…”
Section: E-bike Studiesmentioning
confidence: 99%